Perencanaan Jalan Rigid Pavement Pada Kawasan Perumahan Bunda Asri Kecamatan Bandarkedungmulyo Kabupaten Jombang - Ahmad Irwan Hanafi; Totok Yulianto; Titin Sundari (JURAL RISET RUMPUN ILMU TEKNIK, 2023)
. In fulfilling occupancy eligibility, it is necessary to support facilities and infrastructure. The Bunda Asri housing complex, located in Bandarkedungmulyo, has a land area of ​​32 hectares with a planned construction of 3,000 residential units with 8 types of housing. Residential areas must have infrastructure with a minimum road width of 6 meters as stated in article 15 paragraph 3 of the 2019 Jombang Regency Regional Regulation concerning road infrastructure in residential areas. In this study, the planning used the pd T-2003 method which aims to determine the structure of the rigid pavement of the road at Bunda Asri housing. The results of this study are two types of roads, namely village roads and local roads. On rural roads, the thickness of the rigid pavement layer is 165 mm, the specification for the width of the plate is 2x3.5 m, the length of the plate is 4 m, and the tie rods use D13 threaded reinforcement (0.13 cm), 57.3 cm long, 0.75 cm spacing without using dowel spokes. Whereas for local roads, the thickness of the rigid pavement layer is 170 mm, the specifications for the width of the plate are 2x5 m, the length of the plate is 4 m, and the reinforcement thread D13 (0.13 cm) is used as tie rods, the length is 70 cm and the spacing is 0.75 cm using dowel spokes.